Halftone image watermarking with block-directed parity-matched error diffusion - Kun XIE; Hai-hong ZHENG; Ping ZENG; Tao GUO (Tongxin xuebao)
A robust halftone image watermarking method was proposed.The method was developed in parity domain based on pixel block.Especially,the parity sum of a pixel block was defined by comparing the average of the pixel block with an image-dependent threshold.By altering the pixel block's parity based on noise-balanced block error diffusion,watermark was spread into the host image.Watermark was retrieved by employing each pixel block's parity and majority voting strategy,not referring to the original image.Compared with the state-of-the-art method in parity domain,the re-sults indicate that the proposed method has high watermark rate and watermark rate flexibility.Moreover,it is capable of extracting watermark directly from the attacked watermarked image without quantizing it into a halftone image.And it can achieve high robustness against common attacks and print-and-scan attack of different types of printers and scanners.